Evaluation of Histological Criteria and Immunoserological Testing of Simplified Criteria for the Diagnosis of Autoimmune Hepatitis - Moral, Kenan; Efe, Cumali; Sert, Ayşenur; Şimşek, Berkay; Gökçe, Dilara Turan; Ekmen, Nergiz; Batıbay, Ersin; Kekilli, Murat; Karakan, Tarkan; Ibiş, Mehmet; et al. (Turkish Journal of Gastroenterology, 2025)
Background/Aims: The International Autoimmune Hepatitis (AIH) Group recommends the new histological criteria (HC) (2022) and modified immunoserological testing for diagnosing AIH. The diagnostic utility of the 2022 HC was evaluated. The simplified criteria were also updated with the 2022 HC and immunoserological testing and assessed the diagnostic performance. Materials and Methods: The data of 207 patients (111 AIH, 33 primary biliary cholangitis, 35 drug-induced liver injury, and 28 metabolic dysfunction–associated fatty liver disease) were evaluated. Results: The 2022 HC and the 2008 simplified HC showed 95% vs. 88% sensitivity and 82% vs. 49% specificity for possible/compatible AIH. For likely/typical AIH, sensitivity was 60% vs. 42% and specificity was 98% vs. 95% for the 2022 HC and the 2008 HC, respectively. The area under the curve (AUC) was better for the 2022 HC than for the 2008 simplified HC (0.932 vs. 0.771, P < .001). The updated simplified criteria had a sensitivity comparable with the simplified criteria (88% vs. 87%) but a better specificity (94% vs. 80%) for prob able AIH. The sensitivity was slightly lower (57% vs. 63%), but the specificity was greater (97% vs. 89%) for definitive AIH. The AUC was higher in the updated simplified criteria than in the simplified criteria (0.959 vs. 0.894, P = .016). Conclusion: The 2022 HC showed better sensitivity and specificity than the 2008 simplified HC for AIH. The updated simplified criteria worked well with improved accuracy of AIH diagnosis. Our results suggest that the diagnostic algorithm of AIH should be modified based on recent recommendations. Cite this article as: Moral K, Efe C, Sert A, et al. Evaluation of histological criteria and immunoserological testing of simplified criteria for the diagnosis of autoimmune hepatitis. Turk J Gastroenterol. Published online September 18, 2025. doi: 10.5152/ tjg.2025.25402.